Large net foreign liabilities of euro area countries: Risks, prospects and policy options - Nico Zorell (European Central Bank (ECB), 2017)
Over recent years, several euro area countries have registered large and persistent net foreign liabilities. This paper examines the risks arising from these external stock imbalances, the prospects for their smooth unwinding and the menu of policy options. The paper demonstrates that external stock imbalances remain a source of vulnerabilities in the (former) programme countries and, to a lesser extent, the euro area countries in central and eastern Europe. The net foreign liabilities of these economies stand at levels that are typically associated with an increased susceptibility to external crises. Mechanical projections indicate that the net foreign liabilities of the (former) programme countries will remain at elevated levels over the next decade despite some gradual adjustments, while those of the central and eastern European (CEE) countries could return to more sustainable levels more quickly. There are also vulnerabilities related to the composition of external positions, most notably the unfavourable debt-equity mix in the (former) programme countries. However, the long maturity of public external debt - which is often owed to official creditors - and, in the CEE countries, the prevalence of stable foreign direct investment should mitigate external sustainability risks. Furthermore, the net payments associated with the external positions of the euro area debtor countries are relatively low at the current juncture, although the burden could increase markedly if euro area interest rates were to normalise again. Against this backdrop, a timely and well-designed policy response would provide critical support to the orderly unwinding of the remaining external stock imbalances in the euro area. An optimal policy mix would consist of measures simultaneously fostering GDP growth and sustainable current account improvements in the debtor economies, in particular reforms aimed at enhancing productivity growth and export performance.
Keywords: F21; F32; F34; F36; F45; 330; external adjustment; external imbalances; external sustainability; international investment positions; valuation effects